The effect of BRAFV600E mutation on radioiodine therapy in patients with papillary thyroid carcinoma: a meta-analysis and systematic review - Wang, Bin; Cen, Xiao-Xia; Zhang, Bo-Rui; Zhang, Wei (Frontiers in Endocrinology, 2025)
ObjectiveThe BRAFV600E mutation is one of the most common genetic alterations in papillary thyroid cancer (PTC) and is widely recognized as a factor of poor prognosis. Radioactive iodine (RAI) therapy is recommended after thyroidectomy for patients with high-risk level PTC or distant metastatic PTC. However, the association between BRAFV600E mutation and RAI refractoriness remains controversial and requires additional investigation. This meta-analysis was conducted to evaluate the impact of BRAFV600E mutation on the curative effect of RAI therapy.Materials and methodsElectronic searches for relevant studies were performed in the databases of PubMed, EMBASE, and the Science Citation Index databases, with publication date after January 2005. The 131I uptakes status, response to RAI therapy and recurrence of RAI therapy were extracted and compared using meta-analysis.ResultsWe included 14 eligible studies incorporating 2890 PTC patients, of which 1966 were patients with BRAFV600E mutation. The pooled analysis indicated that BRAFV600E mutation was strongly associated with the loss of iodine avidity (P = 0.0003) in PTC patients, especially in recurrent individuals (P<0.0001). However, BRAFV600E mutation had no significant association on the clinical response or recurrence rate of RAI therapy (P = 0.27 and P = 0.29, respectively).ConclusionThis meta-analysis confirmed the role of BRAFV600E mutation in deterioration of the ability of RAI uptake but provided insufficient evidence to demonstrate that BRAFV600E mutation might impact the clinical response and recurrence after postsurgical RAI therapy for PTC patients.